Analysis of Fogarty Model In Social Studies Learning - Elpalina, Srimutia; Ananda, Azwar; Fatimah, Siti (LANGGAM: International Journal of Social Science Education, Art and Culture, 2024)
Social Sciences (IPS) education has an important role in the educational curriculum to form a holistic understanding of society, culture, history and geography. However, the development of integrated social studies education materials is still faced with a number of challenges, such as teacher unpreparedness, lack of personality competence, and difficulties in integrating concepts from various scientific disciplines in a meaningful way for students. This study aims to investigate the process of formulating and developing integrated social studies educational materials according to Robin Fogarty's contribution and identifying effective strategies to overcome these challenges. The research method used is literature study with a qualitative approach. Data were analyzed using content and descriptive analysis methods from various relevant literature sources. The research results show that the development of integrated social studies education materials according to Robin Fogarty's contribution involves various models, such as the Cellular Model, Connected Model, Nested Model, Sequenced Model, Shared Model, Webbed Model, Threaded Model, Integrated Model, and Immersed Model. Each model provides a different approach to integrating curriculum and facilitating cross-disciplinary learning. Even though each model has its own advantages, each model also has its own limitations and challenges in implementation. The discussion highlights the importance of developing integrated social studies educational materials in developing students' holistic understanding of society and culture and preparing them to become active citizens and participants in a multicultural and global society. The challenges faced in developing this material can be overcome through strategies such as developing learning models that emphasize integration aspects, preparing interesting and relevant teaching materials, as well as training for teachers in implementing an integrated social studies learning approach effectively. It is hoped that this research can make a significant contribution to the development of more effective and relevant social studies curriculum and learning practices in the future.